Granular cell astrocytoma. A case report with immunohistochemical and ultrastructural characterization - Wierzba-Bobrowicz, Teresa; Lewandowska, Eliza; Matyja, Ewa; Dziduszko, Jacek; Koszewski, Waldemar; Stępień, Tomasz; Błażejewska-Hyżorek, Beata (Folia Neuropathologica, 2008)
Granular cell astrocytoma (GCA) is an uncommon type of granular cell tumours (GCTs) in the central nervous system. Granular cells in these tumours are of enigmatic origin. We report a case of cerebral GCA in a 59-year-old man who suffered from diabetes and Addison-Biermer disease. The tumour was localized in the left parietal lobe. Microscopically, the tumour was almost entirely composed of large, polygonal cells with round to oval, granular eosinophilic, PAS-positive cytoplasm. The nuclei were located centrally or eccentrically and sometimes exhibited nucleolar vacuoles. The tumour cells were arranged in nests surrounded by blood vessels and connective tissue. Immunohistochemically, the granular tumour cells were reactive for GFAP and vimentin. They were intensively stained for ubiquitin and some of them were reactive for CD68. Moreover, a lot of stromal cells expressed CD68 reactivity. Ultrastructurally, most tumour cells were round or oval with only a few or without filaments. Their cytoplasm was filled with electron-dense granular material limited by a single membrane and autophagic vacuoles. Another type of tumour cells, present in a significantly lower number, revealed abundant cytoplasm with numerous intermediate filaments, swollen rough endoplasmic reticulum, mitochondria and a few clusters of granular material. Cells with numerous condensed electron-dense, bizarrely-shaped mitochondria and few filaments were occasionally observed. Among granular cells, macrophages with vacuoles and/or lamellar structures were visible. In our case, both immunohistochemical and ultrastructural analysis supported astroglial origin of the granular cell tumour.